The effectiveness of shoe modifications and orthotics in the conservative treatment of Civinini-Morton syndrome: state of art - Colò , Gabriele; Rava, Alessandro; Samaila , Elena Manuela; Palazzolo, Anna; Talesa, Giuseppe; Schiraldi, Marco; Magnan, Bruno; Ferracini , Riccardo; Felli, Lamberto (Acta Biomedica Atenei Parmensis, 2020)
Civinini Morton’s Syndrome (CMS), better known as Morton’s Neuroma, is a benign enlargement that typically affects the third common digital branch of the plantar nerve. It is a common cause of metatarsalgia leading to debilitating pain. It prefers the female gender, with a female to male ratio of 5:1 and an average age of 50 years at time of surgery. Precise aetiology remains under debate, with four etiopathogenetic theories often cited in the literature. Clinical symptoms, physical exam and instrumental evidence are important in assessing and grading the disease. Biomechanics seem to play an important role, especially regarding the usefulness of correct footwear. The first approach in the early stages of this condition usually begins with shoe modifications and orthotics, designed to limit the nerve compression. In order to prevent or delay the development of CMS, shoes should be sufficiently long, comfortable, broad toe-boxed, should bear a flat heel and a sufficiently thick external sole which should not be excessively flexible. Most authors suggested that an insole with medial arch support and a retrocapital bar or pad, just proximal to the metatarsal heads, displaces the pressure sites and can be beneficial to relieve the pain from the pinched nerve. A threshold period of 4.5 months appears to emerge from the results of the analysed studies, indicating that, beyond this period and in neuromas larger than 5-6 mm, orthotics and/or shoes modifications do not seem to give convincing results, proving to be more a palliation for the clinical condition to allow an acceptable life with pain rather than a real treatment.